EVALUASI STRUKTUR BANGUNAN HIJAU INSTITUT TEKNOLOGI SAINS BANDUNG DENGAN METODE PUSHOVER ANALYSIS (STUDI KASUS : TINJAUAN KEAMANAN DAN KESELAMATAN JALUR EVAKUASI) - Kusuma, Catur Bayu Wijaya; Ilham; M. Zain, Arzal (Fakultas Teknik Universitas Muhammadiyah Palu, 2025)
Buildings must be designed to be earthquake resistant for the safety and comfort of its users. This study evaluates the green building structure of the Bandung Institute of Technology using the Pushover Analysis method with an evacuation route case study. The ITSB building has one evacuation access point in the form of a main staircase which is quite open so that it is dangerous if an earthquake or fire occurs. Therefore, the evacuation route needs to be reviewed in terms of structural resilience with the Pushover Analysis method and from the safety side with the safety regulations of the evacuation route. The formulation of the problem in this study is the potential for plastic hinges on the evacuation route which can endanger the evacuation process due to the limited evacuation route. This study itself aims to determine the potential area of ??plastic joints in the ITSB Building obtained from Pushover Analysis. The Pushover Analysis method is carried out by providing a structured lateral load simulation which is then gradually increased to determine the displacement shape of a building structure. Pushover analysis itself in this study is used to obtain information on which parts have the potential to experience plastic joints. This is because plastic hinges are a form of melting or weakening of the structure on the parts of the structural elements that cause the structure to fail to maintain its strength. From the modeling simulation results with the Pushover Analysis method, it was found that the distribution of plastic hinges could endanger building users to evacuate. Data from Pushover Analysis shows that from the plastic hinge distribution mechanism that occurs, the first melting occurs on the landing beam ladder. Where the stairs are the main access to the evacuation route in the ITSB building. To determine the steps to prevent structural damage, a special evaluation is carried out in the area of ??the staircase structure regarding the structural resistance of the staircase area where plastic hinges occur and an evaluation of the comfort and safety of the ladder structure. access stairs during evacuation. The results of data processing indicate that in terms of structural durability, the ladder structure must be strengthened in areas where there are plastic hinges. And in terms of evacuation safety, it is necessary to add a special emergency ladder for disaster evacuation routes.